The Students' Perspective on the Use of Facebook in Writing Class - Bunyamin Ali; Abd Rahman (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2018)
Technology nowadays has many functions in our life. This study aims to explore the students’ perspective on the use of Facebook in a writing class. This study was conducted at English Department, Faculty of Education, State Islamic College (STAIN) of Sorong, West Papua, Indonesia. Ten students of English Education Department (TBI) participated in this study. This study employed a qualitative method. Interview protocol is the main instrument in this study as guides for gathering data during the interview and ease the thematic analysis. This study explores the student perspectives on the use of Facebook in writing classes. Ten students shared their experiences in using Facebook and expressed their opinions about using Facebook in learning. They revealed eight subthemes related to four themes; the beginning of the students in using Facebook, the students’ purposes in using Facebook, their feelings towards the use of Facebook in learning, and their opinion toward the use of Facebook in writing class. Based on the students’ perspective towards the use of Facebook in their learning, this study revealed that most of the students had positive feeling to the use of Facebook in the writing class. This study is expected to give a contribution to English language teaching that Facebook can be a new medium in teaching writing for Islamic Higher Education.